SOVIET COLLECTIVIZATION POLICY IN KHOREZM AND ITS CONSEQUENCES (1929–1959) (Conference Zone, 2022)
On December 21, 1929, the Khorezm District Committee of the Party decided to “construct collective farms” and noted “the obligation to organize one collective farm in all villages until the spring sowing campaign of 1930.”1 As a result, the forced introduction of individual peasants into collective farms rose to such a level that the first secretaries of the district committees of the party completely determined the liquidation of individual farmers as a criterion for their activity.